2020
DOI: 10.18488/journal.62.2020.71.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of MSMEs Performance and its Impact on Province GRDP in Indonesia

Abstract: The purpose of this study was to determine (1) the simultaneous and partial influence of soybean price, consumption of tofu tempeh, the exchange rate of the rupiah against the US dollar, and interest rates factors on MSMEs income, (2) dominant factors on tofu tempeh MSMEs income and (3) the effect of tofu tempeh MSMEs income on the Province GRDP. This research is a quantitative study with a purposive method of determining research areas and a quarterly time series secondary data analysis method from 2009-2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…In terms of macroeconomy, export must be encouraged considering the improvement of MSMEs exported products could boost their actors to increase productivity. It directly leads to increased turnover, which in turn can increase labor absorption (Salim et al, 2020). Related to the role of the government, some studies found that various policies implemented by governments will help SMEs retain human capital as well as increase the demand for their products (Singh et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of macroeconomy, export must be encouraged considering the improvement of MSMEs exported products could boost their actors to increase productivity. It directly leads to increased turnover, which in turn can increase labor absorption (Salim et al, 2020). Related to the role of the government, some studies found that various policies implemented by governments will help SMEs retain human capital as well as increase the demand for their products (Singh et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SMEs also need to be trained on the importance of self-improvement globally. In Indonesia, SMEs resistance to exchange rate fluctuations and contribute significantly to gross regional domestic product (Noor, Susilastuti, & Wildan, 2020). The regulation No.20 year 2008 about SMEs explained that micro-enterprises have annual sales results of at most 300 million rupiahs, small enterprises also have annual sales results of more than 300 million rupiahs up to a maximum of 2.5 billion rupiahs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bank Indonesia (2015) reports that MSMEs can contribute around 60% to GDP (Gross Domestic Product) and create jobs [1]. Culinary is the subsector that contributes the largest to the gross domestic product (GDP) of the creative economy.…”
Section: Introductionmentioning
confidence: 99%